2022
DOI: 10.3390/antiox11061072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of DHA-Induced Regulation of Redox Homeostasis in Retinal Pigment Epithelium Cells through the Combination of Metabolic Imaging and Molecular Biology

Abstract: Diabetes-induced oxidative stress leads to the onset of vascular complications, which are major causes of disability and death in diabetic patients. Among these, diabetic retinopathy (DR) often arises from functional alterations of the blood-retinal barrier (BRB) due to damaging oxidative stress reactions in lipids, proteins, and DNA. This study aimed to investigate the impact of the ω3-polyunsaturated docosahexaenoic acid (DHA) on the regulation of redox homeostasis in the human retinal pigment epithelial (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…With the growing adoption of genome re-sequencing and RNA-Seq technologies, a considerable number of RNA editing sites in the genome of several animal species, Homo sapiens included, have been identified [ 64 ]. Currently, RNA editing in physiological and pathological human retinas remains quite unknown, and it could become clinically relevant in many diseases, such as age-related macular degeneration (AMD), diabetic retinopathy, and other retinal degenerations [ 65 , 66 ]. In the present study, we carried out a comprehensive profiling of RPE cells treated with A2E during a follow-up of four time points (1 h, 2 h, 3 h and 6 h) after exposure and compared them to untreated time zero controls.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing adoption of genome re-sequencing and RNA-Seq technologies, a considerable number of RNA editing sites in the genome of several animal species, Homo sapiens included, have been identified [ 64 ]. Currently, RNA editing in physiological and pathological human retinas remains quite unknown, and it could become clinically relevant in many diseases, such as age-related macular degeneration (AMD), diabetic retinopathy, and other retinal degenerations [ 65 , 66 ]. In the present study, we carried out a comprehensive profiling of RPE cells treated with A2E during a follow-up of four time points (1 h, 2 h, 3 h and 6 h) after exposure and compared them to untreated time zero controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that a more fluid red blood cell membrane may represent a marker of DR in type 1 DM [ 42 ]. In an experimental model, Bianchetti et al found that under induced hyperglycemia human RPE cells treated with ω3-polyunsaturated docosahexaenoic acid (DHA) did not result in cellular apoptosis, suggesting the counteracting effect of DHA on oxidative stress and apoptosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no direct evidence showing intracellular edema of RPE cells, which merits further study with high resolution multi-modal imaging to validate the intracellular edema in vivo both experimentally and clinically. With the advancement of the imaging technologies, metabolic imaging is promising to evaluate the function of RPE cells, which measures the intracellular levels of the metabolites non-invasively and real-timely [ 34 ]. Bianchetti G, et al investigated the effect of docosahexaenoic acid (DHA) on the redox homeostasis in the human retinal pigment epithelial cell line (ARPE-19) under high-glucose conditions, using both metabolic imaging and molecular biology [ 34 ].…”
Section: The Pathogenesis Of Dmementioning
confidence: 99%
“…With the advancement of the imaging technologies, metabolic imaging is promising to evaluate the function of RPE cells, which measures the intracellular levels of the metabolites non-invasively and real-timely [ 34 ]. Bianchetti G, et al investigated the effect of docosahexaenoic acid (DHA) on the redox homeostasis in the human retinal pigment epithelial cell line (ARPE-19) under high-glucose conditions, using both metabolic imaging and molecular biology [ 34 ]. The metabolic imaging, using two-photon microscopy, showed that DHA treatment could increase intracellular nicotinamide adenine dinucleotide plus hydrogen (NADH) to upregulate the production of reductive species in high-glucose + DHA group compared with high-glucose treated cells [ 34 ].…”
Section: The Pathogenesis Of Dmementioning
confidence: 99%
See 1 more Smart Citation